2019
DOI: 10.1002/kin.21307
|View full text |Cite
|
Sign up to set email alerts
|

Automated chemical resonance generation and structure filtration for kinetic modeling

Abstract: This work discusses efficient and automated methods for constructing a set of representative resonance structures for arbitrary chemical species, including radicals and biradicals, consisting of the elements H, C, O, N, and S. Determining the representative reactive structures of chemical species is crucial for identification of reactive sites and consequently applying the correct reaction templates to generate the set of important reactions during automated chemical kinetic model generation. We describe a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…To address the increase in computational requirements for handling additional resonance pathways and structures as well as to identify the representative localized structures, a heuristic-based filtration algorithm will identify representative resonance structures on-the-fly. This approach was shown to correspond well to quantum calculations …”
Section: Molecular Representationsupporting
confidence: 60%
See 2 more Smart Citations
“…To address the increase in computational requirements for handling additional resonance pathways and structures as well as to identify the representative localized structures, a heuristic-based filtration algorithm will identify representative resonance structures on-the-fly. This approach was shown to correspond well to quantum calculations …”
Section: Molecular Representationsupporting
confidence: 60%
“…For surface chemistry, atom types representing generic surface sites have been added, along with quadruple bonds for carbon and silicon. The new set of 16 nitrogen and 26 sulfur atom types has been previously reported, and the remainder of the new atom types are summarized in Table .…”
Section: Molecular Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the existence of a published, experimentally-validated RMG mechanism involving a specific chemistry means some care has been taken inside the RMG database with regard to those chemistries and that at least the most relevant corrections for those reaction conditions are present. For example, Grinberg Dana et al 2018 demonstrated RMG’s capabilities on nitrogen compounds, Class et al 2019 demonstrated RMG’s capabilities on some sulfur chemistries, and Chu et al 2019 demonstrated RMG’s capabilities for small aromatic species. ,, However, the user should keep in mind that all large databases, including the RMG database, likely include some erroneous values  perfection is hard to achieve, and it is challenging to check tens of thousands of numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting MDS of ethene is given in Table S3. Note that it is known that the third-row elements may not follow the octet rule and therefore the present algorithm may overlook some of the possible chemicals involving the third-row elements.…”
Section: Theorymentioning
confidence: 99%